Analyzing Heat Transfer: Experimental and Theoretical Studies on Metal Oxide-Based Binary Nanofluid in Mini Hexagonal Tube Heat Sink - Sriharan, G.; Harikrishnan, S.; Öztop, Hakan Fehmi (Springer/Plenum Publishers, 2024)
The research aimed to explore the thermal performance of a miniature hexagonal tube heat sink (MHTHS) by utilizing three different binary nanofluids. These nanofluids incorporated nanoparticles such as MgO, Al2O3, and CuO, dispersed in base fluids of de-ionized water (DIW) (80 %) and ethylene glycol (EG) (20 %) at different concentrations (0.5 vol %, 1.0 vol %, 1.5 vol %, and 2.0 vol %). Variations in volume flow rate (VFR) and temperature spanned from 10L/h to 50L/h and 10 degrees C to 50 degrees C, respectively. Throughout the study, nanofluids circulated through the hexagonal tube side (HTS) at VFR ranging from 10L/h to 50L/h, while hot DIW flowed through the mini passage (MPS) at a constant VFR of 30L/h. Notably, CuO-DIW/EG nanofluid exhibited an 8.7 % increase in density, and MgO-DIW/EG nanofluids demonstrated a 14 % increase in thermal conductivity at a particle concentration of 2.0 vol %. However, at a higher particle concentration of 2.0 vol %, MgO-DIW/EG nanofluids exhibited a 5.6 % decrease in specific heat. Furthermore, MgO-DIW/EG nanofluids displayed a 79.6 % increase in heat transfer coefficient and a 66.7 % increase in Nusselt number. Although the pumping power and friction factor showed 5.1 % to 20.4 % and 7.5 % increases in particle concentration and Reynolds number, this negative impact did not affect the overall thermal performance of the heat sink. Finally, the study determined that MgO-DIW/EG nanofluid stands out as the most suitable heat transfer fluid for the heat sink.
Keywords: Binary fluids; Friction factor; Hexagonal tube mini channel; Nusselt number; Pumping power